أثر أخلاقيات المهنة في إطار الوقاية من جرائم الفساد الإداري - شيباني ،ميلود; درقيش، هشام رافع (جامعة الوادي University of El Oued, 2024)
إنّ أخلاقيات المهنة هي أساس مسيّر الإدارات العمومية, إذ تعرّف على أساس أنها المعايير التي تحكم سلوك الفرد والجماعة ولديها مصادر منها قانونية كالتشريعات المحلية والدولية وأخرى اجتماعية إذ تعد كضابط قانوني واجتماعي, وفي إطار المقاربة الوقائية للحد من ظاهرة الفساد بأنواعه, الإداري والسياسي والاقتصادي من أجل تهذيب سلوك الموظف والارتقاء به نحو القيام بمهامه المنوطة به بأخلاقية ولامجال للفساد بأنواعه السابقة في إطارها وفي إطار المقاربة العلاجية تعتبر ضابط وآلية لوضع الحجج والآليات لمكافحة الفساد بأنواعه عبر العالم إلا أنه يوجد فساد منتشر عبر كل العالم وله آثار عديدة منها انتشار الرشوة في القطاع العام ,ونجد هناك تسيب إداري يرجع في الأداء الوظيفي المؤسسي للعاملين, لأجل ذلك كان لابد من وضع أخلاقيات العمل التي تُراقب وترافق الأداء الوظيفي المؤسسي وتسعى الى مكافحة قضايا الفساد في العمل التي تضبطها قوانين العمل وأخلاقيات المهنة وفق التشريعات الدولية والمحلية. Professional ethics are the basis of the conduct of public administrations, as they are defined as the standards that govern the behavior of the individual and the group. They have legal sources, such as local and international legislation, and social ones, as they are considered a legal and social control, and within the framework of the preventive approach to reducing the phenomenon of corruption of all kinds, administrative, political, and economic. In order to refine the employee’s behavior and advance him towards carrying out his assigned tasks in an ethical manner, there is no room for corruption of its previous types within its framework and within the framework of the therapeutic approach. It is considered a control and a mechanism for developing arguments and mechanisms to combat corruption of all kinds throughout the world. However, there is corruption spread throughout the world and has many effects, including the spread of bribery in the sector. In general, we find that there is administrative laxity due to the institutional job performance of employees. For this reason, it was necessary to establish work ethics that monitor and accompany institutional job performance and seek to combat corruption issues at work, which are governed by labor laws and professional ethics in accordance with international and local legislation.
ماستر اداري